황연해독탕(黃連解毒湯)이 Hypoxia-reoxygenation에 의해 손상 받은 Mouse Neuroblastoma 2a Cells에 미치는 영향(影響) - 안상훈; Sang Hoon Ahn; 김종우; Jong Woo Kim; 강철훈; Chul Hun Kang; 황의완; Wei Wan Whang (동의신경정신과학회지, 2006)
Objective : This study was designed to asses the effect of Hwangryunhaedoktang and herbs on Mouse neuroblastoma 2a cells damaged by hypoxia-reoxygenation. Method : Mouse neuroblastoma 2a (N2a) cells were measured by MTT assay and LDH assay after 48h hypoxia and 6h reoxygenation. Mouse neuroblastoma 2a (N2a) cells were treated by Hwangryunhaedoktang and herbs. Result :1. Hwangryunhaedoktang was effective on LDH assay of hypoxia and reoxygenation.2. All of herbs were generally effective on LDH assay of hypoxia and reoxygenation.In LDH assay of hypoxia, the effects of herbs depended on concentration.In MTT assay of hypoxia, Coptidis Rhizoma and Gardeniae Fructus were effective.In MTT assay of reoxygenation most of herbs were not effective. But Phellodendri Cortex was effective in high concentration. Conclusion : The results imply that Hwangryunhaedoktang and all herbs of it may have protective effect on dementia and aging.